Production of recombinant human epidermal growth factor fused with HaloTag protein and characterisation of its biological functions - Bai, Mengru; Liu, Yezhuo; Liu, Hongyin; Jia, Yangyang; Tian, Xiangqin; Sun, Changye (PeerJ, 2024)
Epidermal growth factor (EGF) protein is a crucial biomolecule involved in regulating cell growth, proliferation, migration and differentiation, which is used in various therapeutic applications, such as wound healing and tissue regeneration. The production of recombinant EGF is essential for studying its biological function and for its clinical translation. However, EGF protein expressed in prokaryotic cells often occurs in inclusion bodies, and co-expression with soluble tag protein is an effective method to prepare recombinant EGF. In this study, we expressed recombinant human EGF (rhEGF) fused to a HaloTag (Halo-rhEGF) and a large portion of Halo-rhEGF was found in the soluble fraction. Cell growth assay showed that the purified Halo-rhEGF protein could promote the proliferation of fibroblasts (NIH 3T3) and epithelial cells (HaCaT), and significantly increased their viability. Phosphorylation of the intracellular signaling proteins, ERK1/2 and c-Jun, was stimulated by treatment with Halo-rhEGF and the expression levels of proteins regulating cell proliferation were significantly increased. RNA sequencing analysis revealed that rhEGF could increase the transcription of genes enriched in ribosome generation and cell proliferation. Moreover, Halo-rhEGF can be labelled by HaloTag ligand for fluorescence imaging and can be slowly released in tissue repair by binding to anion biomaterials. In conclusion, HaloTag is an efficient fusion tag for rhEGF protein expression, purification and controlled release, and Halo-rhEGF can promote the proliferation and viability of epithelial and fibroblast cells.
Keywords: Epidermal growth factor; HaloTag; Protein expression and purification; Cell viability; HaCaT; RNA sequencing